EXTENDED DOMAIN SPECIFIC MODELING LANGUAGE FOR STRATEGY EDUCATIONAL GAMES AND TRANSFER LEARNING THEORY USING SEGL - NURHADI, NUR AISYAH (2019)
A Domain Specific Modeling Language (DSML) is a visual representation that created to help in presenting ideas, improving communication in a team as well as a tool in problem solving.